Nursery Management of Cantang Grouper (Epinephelus fuscoguttatus-lanceolatus) at Convrete Pond in Balai Perikanan Budidaya Air Payau (BPBAP), Situbondo – East Java. - Steffani Lutfi Yuni firdausi; A Shofy Mubarak (Universitas Airlangga, 2021)
Cantang groupers is an Indonesian fishery commodity is superior and has a high economic value. Cantang groupers (Epinephelus fuscoguttatus-lanceolatus) is an engineered hybrid seeds of cross-breeding between male parent fish giant grouper (Epinephelus fuscoguttatus) with the female parent tiger grouper (Epinephelus lanceolatus). Balai Perikanan Budidaya Air Payau (BPBAP) is one of the balai that have nursed the grouper abstraction with quality seed yields. This Field Work Training with the aim to help financial management of the grouper abstraction in concrete tanks, the factors that need to be considered, challenges that arise in the process of separating grouper and business analysis, used descriptive method of retrieval primary and secondary data. Nursery of cantang groupers seed aims to similize so that it can reduce the level of cannibalism and enchance the fish’s endurance before cultivated on a pond or net cages. Things that need to be prepared in nursery grouping include preparation of containers, seed selection and stocking, grading, growth data collection, feed management, water quality management, pest and disease control, harvesting and marketing. From the results of Field Work Training, the optimal growth rate is 0.55 gr / day and 0.132 cm/day with an increase of 13.2% in 30 days. Optimal growth can occur due to good food management, water quality, and grading.